KONSEP WANPRESTASI DALAM HUKUM PERJANJIAN DAN KONSEP UTANG DALAM HUKUM KEPAILITAN (STUDI KOMPARATIF DALAM PERSPEKTIF HUKUM PERJANJIAN DAN KEPAILITAN) - Kurniawan, Nyoman Samuel (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2014)
Based on the assumption default is debt, the settlement of default case in contract law by using mechanisms of the law of Bankruptcy’s has become a new phenomenon in Indonesian business world. Though it is not infrequently the defendant of bankruptcy intentionally default to reply the counterparty that had already  been  in  default  (exceptio  inadimpleti  contractus  situation).  So  the research problem of this thesis is: Is the concept of default on the law of treaties can be fully applied to the concept of debt in bankruptcy law? T his research used normative legal research methods by using statue approach, case-based approach, comparative approach and the conceptual approach. Analysis of legal materials is done with a qualitative approach to the exploratory nature of interpretive techniques, systematic, evaluative, constructive and argumentative. T he results showed that not all defaults can be expressed as a debt in bankruptcy Law, except if the intended achievement is an achievement in the field of business activity (accounts payable). Default is determined from the agreement, regardless of whether there has been an exchange of rights and obligations or not, while the concept of debt has to be determined from the exchange between the rights and obligations which just happens sided (unilateral halt) though it is not preceded by a written agreement. Beside that, in contract law, tort only accountable to the creditors who have made a covenant only, but in bankruptcy law, the settlement will involve and affect a whole other creditors as well.
Keywords: contract law; bankruptcy law; breach of contract; default; Debt; reciprocal agreements; exceptio inadimpleti contractus